2015
DOI: 10.3390/rs71114559
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Maize Residue Cover Using Landsat-8 OLI Image Spectral Information and Textural Features

Abstract: Abstract:The application of crop residue has become increasingly important for providing a barrier against water and wind erosion and improving soil organic matter content, infiltration, evaporation, temperature, and soil structure. The objectives of this work were to: (i) estimate maize residue cover (MRC) from Landsat-8 OLI images using seven vegetation indices (VIs) and eight textural features; and (ii) compare the VI method, textural feature method, and combination method (integration of textural features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 46 publications
7
27
0
Order By: Relevance
“…In addition, the results show that MLR has a poor performance when using multi-collinearity data to estimate AGB, which confirms the results of a previous study [87]; PLSR performs best in three conventional regression techniques for tackling the multi-collinearity problem, which confirms the results of a previous study [87]. Thus, PLSR is a useful tool that can be used to estimate several response variables simultaneously, while accounting for multi-collinearity variables [88].…”
Section: Analysis and Selection Of Vegetation Indexessupporting
confidence: 81%
“…In addition, the results show that MLR has a poor performance when using multi-collinearity data to estimate AGB, which confirms the results of a previous study [87]; PLSR performs best in three conventional regression techniques for tackling the multi-collinearity problem, which confirms the results of a previous study [87]. Thus, PLSR is a useful tool that can be used to estimate several response variables simultaneously, while accounting for multi-collinearity variables [88].…”
Section: Analysis and Selection Of Vegetation Indexessupporting
confidence: 81%
“…Previous studies have proposed numerous indices to estimate CRC. Table 1 lists several promising spectral-based indices for CRC, such as the simple tillage index (STI) [32], the SRNDI [34], the NDSVI [33], DFI [30], the normalized difference tillage index (NDTI) [32], and the hyperspectral CAI [20]. The hyperspectral SINDRI is calculated from the: (i) hyperspectral bands 2210 and 2260 nm [36], (ii) ASTER SWIR bands 6 and 7 [36], and (iii) from the currently functional Worldview-3 SWIR bands 6 and 7 [14].…”
Section: Traditional Crop Residue Cover Spectral Indicesmentioning
confidence: 99%
“…An SI is a combination of two or more remotely detected reflectance bands. Estimates of CRC based on remote-sensing data are quantified by using SIs, such as the dead fuel index (DFI) [30], the normalized difference index (NDI, NDI5, and NDI7) [31], the normalized difference tillage index [32], the normalized difference senescent vegetation index (NDSVI) [33], the short-wave near-infrared normalized difference residue index (SRNDI) [34], the cellulose absorption index (CAI) [35], the shortwave infrared normalized difference residue index (SINDRI) [36], and lignin cellulose absorption [37]. A linear or exponential empirical CRC-estimation equation can be constructed and applied to remote-sensing data by using SI methods.…”
Section: Introductionmentioning
confidence: 99%
“…They found that bands of 5 and 7 due to covering the region near 2100 nm are suitable for the estimation of the SSR. Earlier studies applied NDTI and STI indices to multispectral Landsat 6, 7, and 8 images [19][20][21] and obtained accurate results.…”
Section: Introductionmentioning
confidence: 99%
“…The lignin cellulose index and the shortwave infrared normalized difference residue index were two other multispectral tillage indices based on advanced spaceborne thermal emission and reflection radiometer data, which are superior to the Landsat-based tillage indices, but not as good as the CAI in terms of mapping and characterizing the SSR [23]. Jin et al [21] increased the accuracy of the detection of SSR by integrating Landsat-8 based tillage indices and gray level co-occurrence matrix (GLCM) textural features.…”
Section: Introductionmentioning
confidence: 99%